Kajian Status Mutu Air Laut Terhadap Kehidupan Ekosistem di kawasan Teluk Tomini - Jusman Jusman (Biocelebes, 2008)
The research about status study of sea water quality to life ecosystem in Gulf of Tomini area. Study conducted in January, February, and March of location is territorial sea water the Regency of Parigi Moutong which is gone the round of some subdistrict region ( Sausu, Parigi, Ampibabo, Kasimbar, Tinombo,Tinombo South Arch, Tomini, Mepanga, Bolano Lambunu, Toapa, and Moutong). For the method of data collecting, in principle data collected consisted of the primary data, and secondary data. Based on the perception data / measurement to sea water quality, in general sea water quality in territorial of forest mangrove, sea grass , coral compose , maritime area wisata, and area of territorial water of port perceived to fulfill permanent sea water quality for the biota pursuant to ministrial decree of State of Environment No. 51 year 2004. Average result of quality measurement sea water by in situ, like brightness parameter, temperature, oil coat, pH, salinity, and dissolved Oxygen still below/under permanent of sea water quality.From inferential the result that status of sea water quality to life ecosystem in area Gulf of Tomini not yet impure/destroy so that potency of the happening of defensible environmental degradation. Key words : Sea Water Quality, Ecosystem, Gulf of Tomini.